An integrative review on the use of aromatic plants found in the Amazon to promote herbal medicine (Research, Society and Development, 2021)
Due to their therapeutic properties, aromatic plants are widely used by the population for medicinal, flavoring, flavoring and scientific studies regarding pharmacological actions: anti-inflammatory, antispasmodic, antioxidant, antiseptic, antimicrobial, calming, carminative, among others. Therefore, the objective is to facilitate the production of aromatic plants to help the population and health professionals to seek knowledge about the pharmacological and physiological effects of the bioactive compounds of each plant in favor of human health, through herbal medicine. The work was based on research of articles published in the period from 2013 to 2021, according to the literature review in scientific platforms: SciELO and PUBMED, with respective selections and readings of articles from July to September. In total, 30 articles were obtained, from which those that contained repetitions and did not present a context compatible with the theme were excluded, leaving only 21 selected articles. Based on the bibliographical review, 10 species of aromatic plants were selected (Rosecrim; Oregano; Brazilian Boldo; Arruda; Common Mint; Lemongrass; Lemongrass; Alfavaca; Sage; Lavender), with their respective information: scientific name, name popular, used part of the plant, pharmacological property, therapeutic indication. The study identified, within phytotherapy and traditional medicine, different approaches and customs regarding the correct use in the management of medicinal plants. In addition to contributing to the dissemination of knowledge about this class of (aromatic) plants, the present study provides tools based on reading about how to use them for the most efficient preparation of these species reviewed here.